2016
DOI: 10.1103/physrevb.94.035133
|View full text |Cite
|
Sign up to set email alerts
|

Variational optimization with infinite projected entangled-pair states

Abstract: We present a scheme to perform an iterative variational optimization with infinite projected entangled-pair states (iPEPS), a tensor network ansatz for a two-dimensional wave function in the thermodynamic limit, to compute the ground state of a local Hamiltonian. The method is based on a systematic summation of Hamiltonian contributions using the corner transfer-matrix method. Benchmark results for challenging problems are presented, including the 2D Heisenberg model, the Shastry-Sutherland model, and the t-J … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
230
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(234 citation statements)
references
References 68 publications
3
230
1
Order By: Relevance
“…On the other hand, it is a major goal to extend this type of real-time simulation technique to more than one spatial dimension using projected entangled pair states (PEPS) [4]. The major progress on PEPS algorithms in the last decade [93][94][95][96][97][98][99][100][101][102] in combination with recent promising PEPS and TNS results for higher-dimensional gauge theories [103][104][105][106][107] makes us confident that this will be realized in the foreseeable future.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is a major goal to extend this type of real-time simulation technique to more than one spatial dimension using projected entangled pair states (PEPS) [4]. The major progress on PEPS algorithms in the last decade [93][94][95][96][97][98][99][100][101][102] in combination with recent promising PEPS and TNS results for higher-dimensional gauge theories [103][104][105][106][107] makes us confident that this will be realized in the foreseeable future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the method is very promising for future applications using PEPS. When we finalize the work, we get to know that variational optimization methods including the gradient method, 40,41 have been applied to optimize infinite PEPS wave functions where the gradients are calculated via direct contractions. It has also been shown that variational results are better than the best known full update results, consistent with our findings.…”
Section: Benchmark Resultsmentioning
confidence: 99%
“…Although some interesting studies of gauge theories with PEPS have appeared [92][93][94][95][96], at present, the need for a large number of variational freedom when approaching the continuum limit, is still hindering a truly variational study of gauge field theories [97]. Fortunately, in the last years the PEPS methods have significantly improved [98][99][100][101][102][103][104][105][106][107]. In particular, for some models the PEPS framework can already compete with state-of-the-art results of Monte-Carlo simulations [103].…”
Section: Discussionmentioning
confidence: 99%